Effect of solvent and atmosphere on product distribution, hydrogen consumption and coal structural change during preheating stage in direct coal liquefaction. (1st January 2018) - Hao, Pan; Bai, Zongqing; Hou, Ranran; Xu, Junli; Bai, Jin; Guo, Zhenxing; Kong, Lingxue; Li, Wen
Highlights: Product distribution and change of coal properties under non exterior hydrogen source conditions were explored at 200–350 °C. Effects of H2 and N2 atmosphere on product distribution obtained by tetralin and 1-MN preheating treatment were evaluated. Hydrogen consumption from tetralin and gas H2 at 350 °C was quantified. Decomposition of COOH and CO was not affected by the preheating solvent and atmosphere but relied on temperature. Abstract: In order to study the necessity of hydrogen source at preheating stage of direct coal liquefaction, product distribution, hydrogen consumption, and coal structural change of Hami sub-bituminous coal (HM) with 1-methylnaphthalene (1-MN) and tetralin respectively were investigated under hydrogen and nitrogen atmosphere. The results show that oil could be generated from coal itself with 1-MN under N2 and the yield increases with temperature rising at the range of 200–350 °C, whereas only 4.94% oil is obtained at 350 °C. Moreover, volatiles and H/C ratios of pretreated coal decrease dramatically above 250 °C. At 350 °C, preheating with gas phase H2 in 1-MN promotes oil yield to 10.42%. In the presence of tetralin, oil yields of 28.55% and 26.15% are achieved under N2 and H2 at 350 °C, respectively. Approximately same total hydrogen consumption is observed under N2 and H2 with tetralin, and the hydrogen consumption from tetralin is higher than that from H2 . With the addition of hydrogen sources, aromaticity of the residual solid decreases and reactivity increases. Decomposition of oxygen-containing functional groups like COOH and CO is not affected by the preheating solvent and atmosphere but relies on temperature. In addition, pretreated solid samples achieve increasing oil yield and conversion in the subsequent liquefaction with their rising thermal reactivity and H/C ratios.